Inovasi Pembelajaran Ips Yang Inklusif Melalui Pemanfaatan Kampung Adat Cikondang Sebagai Laboratorium Alam Dan Budaya - Handani, Sari Sri; Mustika, Dena; Supriatna, Nana (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
Cikondang Traditional Village has a rich culture and local wisdom that still maintains traditions, customs and cultural practices. This research aims to develop an inclusive social studies learning model by utilizing Cikondang Traditional Village as a natural and cultural laboratory. The method in this research uses a mixed methods approach, which is a combination of qualitative and quantitative methods. This approach allows researchers to obtain comprehensive and in-depth data on the effectiveness of the developed learning model. The results showed that integrating the local potential of Cikondang Traditional Village into social studies learning can provide a more contextual, authentic, and meaningful learning experience for students. In addition, social studies learning currently also faces problems of inequality of access and inclusiveness. Students with different social, economic and cultural backgrounds often do not get equal opportunities to participate and understand the subject matter well. Thus, innovation is needed in social studies learning that not only makes the subject matter more relevant and contextual, but also inclusive for all learners through natural and cultural laboratories that actually exist in the community, namely the Cikondang traditional village.